Analysis of Medico Legal Autopsies - A 6 year Retrospective Study (Indian Internet Journal of Forensic Medicine and Toxicology, 2010)
Unnatural deaths claim a considerable number of lives, with major share being contributed by Road Traffic Accidents (RTA). In this retrospective study, 908 medico-legal autopsies conducted at the mortuary of the department of Forensic Medicine, J.N.Medical College, Belgaum, Karnataka, during the period from 01-01-2004 to 31-12-2009 were analysed. Victims were predominantly males (75.9%) and maximum number of cases were of RTAs (56%). Majority of the victims were in the age group 21-30 years (32.5%). Most of the RTAs occurred in the evening hours (38.4%) and during summer (39.4%). Motorcyclists were the most commonly involved victims (50.4%) and most common offending vehicle was heavy motor vehicle (16.7%). More than 50% of victims of RTAs died within one week of the accident. Among the cases of poison ing, majority of cases were due to organ phosphorus pesticide (53.6%). In cases of burns, death due to dry heat (86.8%)) was more than moist heat (13.2%) and in maximum number of cases TBSA involved was 81-90% (22.2%). In most of the cases of assault the weapon used was hard blunt weapon (56%).
Keywords: Medico-legal autopsy; Unnatural death; RTA; Burns; Poisoning